Caracterização de uma estação de tratamento de esgoto por zona de raízes utilizando variáveis abióticas e microbiológicas - Lohmann, Gabriele (2011)
Wastewater root zone treatment systems are constituted of a filter bed planted with emergent macrophytes. A low cost technology with treatment potential proven in numerous studies, the root zone Wastewater Treatment Station (WTS) have great potential to solve the problem of lack of wastewater collection and treatment in small communities. This study aimed to characterize a root zone WTS with vertical flow on the basis of abiotic and microbiological variables. Through the technique of plate count and the multiple tube method was possible to estimate the density of total fungi, heterotrophic bacteria, total coliforms, Escherichia coli, nitrate-reducing bacteria, denitrifying bacteria and sulfate-reducing bacteria in the different strata of the system. In addition to the microbiological analysis the abiotic variables temperature, pH, dissolved oxygen, ammonia nitrogen, nitrite, nitrate, total nitrogen, orthophosphate, Chemical Oxygen Demand (COD) were evaluated. Analyses were performed in eight locations, one related to raw wastewater, one of treated effluent, three corresponding to the root zone interface and three to the sand filter, in a total of seven samples during a seasonal cycle. In 5 samples did not exhibit a reduction in the MPN of E. coli, only in Sample 1 (C1) and Sample 7 (C7) was observed approximately 66% and 97% reduction, respectively. Denitrifying bacteria in most spots and sulfate reducers, with the exception of the Sample 3 (C3) were determined in the amount of 1600 MPN.100mL-1. The density of nitrate-reducing bacteria ranged in most samples, from 1.8 MPN.100mL-1 to 19 MPN.100mL-1. The WTS was efficient for the removal of COD and phosphorus, the latter with removal percentage ranged from approximately 37% to 69 %. The concentration of ammonia-N was reduced in all samples, except for C3. The pH remained near neutrality and the concentration of dissolved oxygen increased in the region of the sand filter. Throughout the study period was observed a less growing of the plants. With the results of quantification it was possible verify that biodegradation is more intense in the first 50 cm of the WTS. It was observed significant reduction in the density of microorganisms in the sand filter compared with the root zone. Factors such as age of the station, which allowed the formation of a biofilm in the filter of gravel, the presence of sand filter and the availability of organic matter may be involved in the reduction of microorganisms. In summary it can be concluded that the WTS was efficient for removal of microorganisms, but only during periods of low rainfall.